Uses of inorganic chemistry in medicine - Farrell, Nicholas, 1948- (Royal Society of Chemistry, 1999)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. Metal-based drugs are a commercially important sector of the pharmaceutical business, yet most bioinorganic textbooks lack the space to cover comprehensively the subject of metals in medicine. Uses of Inorganic Chemistry in Medicine approaches an understanding of the topic in a didactic and systematic manner. The field of inorganic chemistry in medicine may usefully be divided into two main categories - drugs which target metal ions in some form, whether free or protein-bound, and secondly, metal-based drugs where the central metal ion is usually the key feature of the mechanism of action. This latter category can further be subdivided into pharmacodynamic and chemotherapeutic applications, as well as those of imaging. The book summarises the chemical and biological studies on clinically used agents of lithium, gold and platinum, as well as highlighting the research on prospective new drugs, including those based on vanadium and manganese. The coverage allows a clear distinction between pharmacodynamic and therapeutic properties of metal-based drugs and focuses not only on those clinical agents in current use, but also on new drugs and uses. This book serves to fill an important niche, bridging bioinorganic and medicinal chemistry and will undoubtedly be of use to senior undergraduates and postgraduates, as well as being an invaluable asset for teachers and researchers in the discipline.
Keywords: Pharmaceutical chemistry.; Chemistry, Inorganic.; elektronické knihy; electronic books